La produccion y la investigacion del cultivo de frijol en vainita (Phaseolus vulgaris) en el Peru - Salazar N., G. (International Center for Tropical Agriculture, 1987)
The most important limiting factors for snap bean cultivation in Peru are lack of improved var. seed, nematodes, rust, BCMV, shoot and pod borers, and mining fly. To solve these problems, it is necessary to develop an efficient snap bean seed production system and promote commercialization systems that stimulate production and consumption. The establishment of an international exchange of snap bean material is recommended as well as the distribution of early generation material for adaptation trials. (CIAT)